Romanens sølvnitrat: Det antisentimentale i den danske oplysningslitteratur - Zetterberg-Nielsen, Simona (K&K - Kultur og Klasse, 2021)
This article explores the possibility of sentimentality in the Danish Enlightenment by investigating the Danish novels of the late eighteenth century. In Denmark, it was not until the 1780s that marriage, upbringing and relationships of love became the focus of the novel. By that time, the European current of sentimentalism had already turned to anti-sentimentalism. Therefore, the Danish novels never embraced the sentimental tendency, but instead discussed well-renowned sentimental novels in order to articulate a morality directed by reason. The article elucidates how Charlotta Dorothea Biehl’s collection Moralske fortællinger [Moral Tales] (1781-1782) and her epistolary novel Brevvexling imellem fortrolige Venner [Epistolary Correspondence between Intimate Friends] (1774), Knud Lyne Rahbek’s novels Hanna von Ostheim eller den kierlige Kone [Hanna von Ostheim and the loving wife] (1790) and Eulalia Meinau (1798, 1806) and Charlotte Baden’s Den fortsatte Grandison [The Continued Grandison ] (1782) discuss some of the most famous sentimental novels of the time: Wolfgang Goethe’s Die Leiden des jungen Werthers (1774), Martin Miller’s Siegwart, eine Klostergeschichte (1776), Rousseau’s Emile and Samuel Richardson’s The History of Sir Charles Grandison (1753). Biehl, Rahbek and Baden used the internationally famous novels as discussion partners, material for parody and as points for continuation, with the aim of warning against sentimentality and promoting a reading practice that facilitated reason and a virtuous living. Finally, the article suggests that the eighteenth century current of anti-sentimentalism in Denmark might have survived into the next century.